A weight of evidence framework for environmental assessments: Inferring qualities. (21st July 2017) - Suter, Glenn; Cormier, Susan; Barron, Mace
ABSTRACT: The weighing of heterogeneous evidence such as conventional laboratory toxicity tests, field tests, biomarkers, and community surveys is essential to environmental assessments. Evidence synthesis and weighing is needed to determine causes of observed effects, hazards posed by chemicals or other agents, the completeness of remediation, and other environmental qualities. As part of its guidelines for weight of evidence (WoE) in ecological assessments, the US Environmental Protection Agency has developed a generally applicable framework. Its basic steps are these: assemble evidence, weight the evidence, and weigh the body of evidence. Use of the framework can increase the consistency and rigor of WoE practices and provide greater transparency than ad hoc and narrative‐based approaches. Integr Environ Assess Manag 2017;13:1038–1044. Published 2017. This article is a US Government work and is in the public domain in the USA. Key Points: A general framework for weighing evidence in environmental assessments includes assembling evidence, weighting the evidence, and weighing the body of evidence. Heterogeneous evidence should be weighed to determine qualities such as causation of observed effects, adverse outcome pathways, and hazards posed by chemicals. The properties to be weighted are relevance, strength, reliability, and collective properties such as the number and diversity of pieces of evidence. A formal consistent method for weighing evidence can increase the transparency and defensibly of assessments.